DESIGNING COMIC AS LOCAL FOLKLORE BASED-MATERIALS TO SUPPORT NARRATIVE TEXT READING - Nurfadhilah, Aussie; Salam, Urai; Rezeki, Yanti Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this research was to design teaching material to support students in learning of narrative text reading with the local folklore comic. The researcher took the folklore from West Kalimantan story book collection. The method of this research was a development research. In conducting this research, the researcher used ADDIE approach (Analyze, Design, Develop, Implement, and Evaluation). The first three phases were the phases that the researcher used in doing the research. To design the product, the researcher first analyzed the students and teacher condition and also their problems and needs toward English teaching and learning process. After that the researcher selected and collected the interesting materials then started to make a comic. Futhermore, the researcher asked two experts to validate the comic whether it was appropriate or not to support the teaching and learning process of narrative text reading by using an assessment rubric. The result shows that the product was classified as Very Good with the score of percentage 93%. It meant that the comic can be used to support teaching and learning narrative text reading. Keywords: Development Research, Comic, Narrative text, Reading.